Development of an aquaponic system using ablution greywater for recreational purpose - Che Saad, Muhammad Adib; Mohideen Batcha, Mohd Faizal; Razali, Mohd Azahari; Abdul Rahman, Ramhuzaini; Ahmad Nazri, Mohd Ariff; Lam, Hong Yin; Ishak, Maizul; Yusop, Azli (Penerbit UTHM, 2020)
The ablution ritual consumes large quantities of water, especially in mosques and public prayer rooms, where the greywater is allowed to run free and drain away. In Malaysia, most ablution system consists of a line of water taps with a drainage trough to carry the greywater to main drains. Some decent water is lost in the process as the tap is left running. In view of unnecessary waste, a simple recycling system can be designed to collect, treat and reuse the ablution water within a close-loop system for non-drinking applications, such as toilet flushing, general washing, plants watering and flowerbed cultivation. Therefore, this study was conducted to recover and reuse the ablution greywater that produced from Masjid Sultan Ibrahim with an aquaponic system. The aquaponic system involves the use of fish as a source of nutrients for the plant's growth, while the plants filter the water for the fish. In addition, the aquatic system model has its own attraction value that is very compatible with the landscape of the Masjid Sultan Ibrahim and at the same time it also provides recreational activities.